2012
DOI: 10.3989/scimar.03411.07c
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organic and conventional production methods on sea bream growth, health and body composition: a field experiment

Abstract: SUMMARY: This study aimed to develop a better understanding of organic sea bream aquaculture production in Greece, in particular its consequences for fish growth, health and body composition, and to propose and update standards for sustainable organic sea bream farming. Gilthead sea bream were kept in sea cages at densities of 4 kg m -3 (organic) and 15 kg m -3 (conventional), and were fed organically produced feed (45% crude protein, 14% fat) or conventional feed (46% crude protein, 17% fat). The amino acid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
0
22
1
Order By: Relevance
“…Nevertheless, the production rate of dissolved and particulate nitrogenous waste by farmed salmon has been estimated (Davies 2000; Mente et al, 2006). Recently, the high or low sea bream ( Sparus aurata ) density in aquaculture cages was suggested to cause significant differences in bacterial cell numbers in response to higher or lower amounts of excreted material from the fish (Mente et al, 2012). The development of commercial rearing facilities that are in line with advances in research for optimal culture conditions will facilitate the further growth of sustainable ornamental aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the production rate of dissolved and particulate nitrogenous waste by farmed salmon has been estimated (Davies 2000; Mente et al, 2006). Recently, the high or low sea bream ( Sparus aurata ) density in aquaculture cages was suggested to cause significant differences in bacterial cell numbers in response to higher or lower amounts of excreted material from the fish (Mente et al, 2012). The development of commercial rearing facilities that are in line with advances in research for optimal culture conditions will facilitate the further growth of sustainable ornamental aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…), can result in quality changes that are then difficult to trace to a particular cause. For instance, the work of Mente et al (2012), one of the few available studies with gilthead seabream, showed that organically produced seabream had higher growth, moisture and protein content and lower muscle lipid content. However, the higher growth can be a result of the lower stocking densities used or of the quality of the organic feed.…”
Section: Farming Practices: Stressful Events At Slaughtermentioning
confidence: 99%
“…Nevertheless, the ratio of n-3 to n-6 polyunsaturated fatty acids was significantly higher in organic than in conventional fish. MENTE et al (2012) studied the effect of organic and conventional production methods on gilthead sea bream (Sparus aurata L.) specimens, from 10 g to 350 g (commercial size) in sea cages. The gilthead sea bream specimens were kept at densities of 4 kg/m 3 (organic) and 15 kg/m 3 (conventional) and were fed with organic food (45% crude protein, 14% fat) or conventional feed (46% crude protein, 17% fat).…”
Section: Introductionmentioning
confidence: 99%